The great social laboratory : subjects of knowledge in colonial and postcolonial Egypt - El Shakry, Omnia S., 1970- (Stanford University Press, 2007)
This study charts the development of the human sciences - anthropology, human geography, and demography - in late 19th and 20th century Egypt. Tracing both intellectual and institutional genealogies of knowledge production, it examines social science through a broad range of texts and cultural artifacts, ranging from the ethnographic museum, to architectural designs, to that pinnacle of social scientific research - 'the article'. The book explores the interface between European and Egyptian social scientific discourses, and interrogates the boundaries of knowledge production in a colonial and post-colonial setting.